Condition, Potential Recovery Rate, and Productivity of Lichen (Cladonia spp.) Ranges in the Finnish Reindeer Management Area - Kumpula, Jouko; Colpaert, Alfred; Nieminen, Mauri (ARCTIC, 2000)
The focus of the work was to investigate dependency between reindeer density and lichen (Cladonia spp.) ranges in the Finnish semidomesticated reindeer management area. Secondly, we formed a model on the recovery rate of ungrazed woodland lichen ranges (29 sites) after forest fires to evaluate the potential productivity and time needed for Finnish lichen ranges to recover at optimal production. During 1974-95, 59% of the variation in mean semidomesticated reindeer density (range: 0.7-3.0 reindeer/km² of the total land area) among the reindeer herding districts in Finland was explained by the proportion of land area covered by lichen ranges in these districts. Reindeer densities were highest in the districts where lichen ranges covered 20% to 30% of the area. Reindeer density on the total land area did not explain the condition of lichen ranges, but 58% of the condition was explained by the reindeer density on the lichen ranges. A condition level for lichen ranges of 1000 kg dry matter per hectare (d.m./ha) of lichen biomass can be considered adequate to ensure survival of reindeer and continued production of lichen. To maintain this level within the sedentary Finnish grazing system, winter reindeer densities on lichen ranges must remain below 5-7 reindeer/km². According to our model, the maximum amount of living lichen in the woodland lichen stand at the climax stage is on average about 7000 kg d.m./ha. The maximum annual yield of lichen (175 kg d.m./ha) is produced by lichen stands that contain 2600-2800 kg d.m./ha of living lichen. Using our model and our 1995-96 data, we calculated that the average lichen biomass on lichen ranges in the Finnish reindeer management districts was 13.0% of this optimum, and the average lichen production was 36% of the possible maximum annual yield. Our model indicates that the Finnish lichen ranges would have to remain ungrazed for an average of 18 years to recover to maximum production levels. However, the average time needed for the lichen ranges to recover to the level of ...